Ginseng protein protects against mitochondrial dysfunction and neurodegeneration by inducing mitochondrial unfolded protein response in Drosophila melanogaster PINK1 model of Parkinson's disease. (30th January 2020) - Liu, Meichen; Yu, Shiting; Wang, Jiawen; Qiao, Juhui; Liu, Ying; Wang, Siming; Zhao, Yu
Abstract: Ethnopharmacological relevance: Historical literature and pharmacological studies demonstrate that ginseng, one of the most popular herbal medicines in China, holds potential benefits for Parkinson's disease (PD). Aim of the study: Studies in Drosophila melanogaster (Dm) have highlighted mitochondrial dysfunction upon loss of PTEN-induced putative kinase 1 (PINK1) as a central mechanism of PD pathogenesis. Using PINK1 B9 mutant Dm, we aimed to explore the therapeutic action of ginseng total protein (GTP) on PD and provide in-depth scientific interpretation about the traditional efficacy of ginseng. Materials and methods: We first used gel chromatography to purify GTP and confirmed its molecular weight by SDS-PAGE. Effects of GTP on PINK1 B9 mutants, which were supplied with standard diet from larvae to adult stages, were assayed in flies aged 3–6 (I), 10–15 (II), and 20–25 (III) days. Parkinson-like phenotypes were analyzed by evaluating lifespan, dopaminergic neurons, dopamine levels, and locomotor ability. Mitochondrial function was assessed by evaluating ATP production, respirometry, and mitochondrial DNA. In addition, reactive oxygen species were measured using dihydroethidium and 2′, 7′-dichlorodihydrofluorescein diacetate staining. PD-related oxidative stress was simulated by paraquat and rotenone, and mitochondrial membrane potential was measured using JC-10 reagent. Protein and mRNA expression was detected by Western blot and real-time quantitative reverse transcription polymerase chain reaction, respectively. Results: This study demonstrates for the first time that GTP treatment delays the onset of a Parkinson-like phenotype in PINK1 B9 Dm, including prolongation of lifespan and rescue of climbing ability, as well as rescue of the progressive loss of a cluster of dopaminergic neurons in the protocerebral posterior lateral 1 region, which was accompanied by a significant increase of dopamine content in the brain. In addition, GTP notably reduced the penetrance of abnormal wing position, indicating a strong inhibitory effect on indirect flight muscle degeneration. We further showed that GTP could promote maintenance of mitochondrial function and protect mitochondria from PD-associated oxidative stress by activating the mitochondrial unfolded protein response (UPR mt ). Conclusions: GTP protected against mitochondrial dysfunction and neurodegeneration by inducing UPR mt in the Dm PINK1 B9 model of PD. Our results suggest that GTP is a promising candidate for PD, and reveal a new mechanism by which ginseng is neuroprotective. Graphical abstract: Image 1